A new Alestopetersius (Characiformes: Alestidae) from the Kwilu River (Kasai basin) of central Africa; with a phylogeny for the genus and synonymy of Duboisialestes - Munene, José Justin Mbimbi Mayi; Stiassny, Melanie L.j. (Zootaxa, 2012)
A new Alestopetersius is described from the Kwilu River in the Kasai basin of the Democratic Republic of Congo. Alesto-petersius conspectus, new species, is readily distinguished from all congeners based on attributes of squamation and col-oration. It is distinguished from “Duboisialestes” tumbensis by tooth morphology and in the possession of a distinctivecaudal-fin pigmentation patterning consisting of a median black band extending to the caudal-fin margin and flanked bydense black bands in both upper and lower fin lobes. “Duboisialestes” bifasciatus, which shares similar caudal-fin pig-mentation patterning, is distinguished from A. conspectus by the absence of a broad mid-lateral band on the body, and bytooth morphology. Results from an analysis of the relationships and generic composition of the Alestidae provide supportfor the monophyly for Alestopetersius inclusive of the members of the genus Duboisialestes, which are placed into syn-onomy with the former.Une nouvelle espèce de Alestopetersius est décrite de la rivière Kwilu dans le bassin du Kasai de la RépubliqueDemocratique du Congo. Alestopetersius conspectus, nouvelle espèce, se distingue très facilement de tout ses congénèressur les attributs de la squamation et coloration. Cette espèce est distinguée de “Duboisialestes” tumbensis par la morphol-ogie des dents et par la posséssion d'un type de pigmentation de la nageoire caudale composée d’une bande noire médianes'étendant de la marge de la caudale et flanquée de denses bandes noires dans les deux lobes supérieur et inférieur de lanageoire. “Duboisialestes” bifasciatus qui partage le même type de pigmentation de la nageoire caudale, se distingue deA. conspectus par l'absence d'une large bande mi-latérale sur le corps, et par la morphologie des dents. Les résultats d'uneanalyse des relations et de la composition générique du Alestidae fournissent un soutien pour la monophylie des Alestopetersius incluant les membres du genre Duboisialestes, qui sont placés en synonymie avec le genre précèdent.